2004
DOI: 10.1113/expphysiol.2004.027953
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of visceral function by selective stimulation of the left vagus nerve in dogs

Abstract: The superficial regions of the left vagus nerves of a dog were selectively stimulated with 39-electrode spiral cuffs having 13 circumferential groups of three electrodes (GTE) to modulate the function of the innervated internal organs and glands. Under general anaesthesia, the cuffs were chronically implanted around the nerve in the neck in two adult Beagle dogs and remained viable for 16 months. The regions were stimulated with biphasic, rectangular current pulses (2 mA, 200 µs, 20 Hz) delivered to the group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The effect of stimuli via vagal afferents on the urinary bladder function indicates that these afferents could be targeted in order to manage urinary bladder problems. Selective electrical stimulation of cervical vagus nerve, via implanted electrodes in dogs, resulted in modulation of respiratory, cardiac, vesical, and glandular functions 25. In addition, vagus nerve electrical and magnetic stimulation was shown to have the potential of managing problems affecting the heart function and bowel motility 26, 27.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of stimuli via vagal afferents on the urinary bladder function indicates that these afferents could be targeted in order to manage urinary bladder problems. Selective electrical stimulation of cervical vagus nerve, via implanted electrodes in dogs, resulted in modulation of respiratory, cardiac, vesical, and glandular functions 25. In addition, vagus nerve electrical and magnetic stimulation was shown to have the potential of managing problems affecting the heart function and bowel motility 26, 27.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] In canines, this is supported by findings that electrical stimulation of the vagus nerve in the neurally intact dog has no effect on bladder pressure. 8 In humans, complete spinal cord injury does not block perceptual responses to genital self-stimulation 9 and functional magnetic resonance imaging (FMRI) shows activation of the inferior region of the solitary nucleus (medullary origin of the vagus nerve) induced by cervical self-stimulation in complete spinal cord injured women. 10 Very recent fMRI findings during bladder filling in patients with complete spinal cord injury demonstrate activation of brainstem nuclei that are involved in vagal nerve afferents and this significantly correlates with the patients' reports of bladder sensation.…”
Section: Introductionmentioning
confidence: 99%
“…Although hepatic glucose flux is primarily under the direct control of insulin (Cardin et al, 2002), numerous studies have found that stimulating vagal efferents alters peripheral glucose flux and insulin secretion (Shimazu and Fujimoto, 1971; Shimazu, 1971; Rohner-Jeanrenaud et al, 1983; Berthoud et al, 1990; Rozman and Bunc, 2004; Peitl et al, 2005). Moreover, intact vagal fibers and capsaicin-sensitive afferents are required for the normal regulation of hepatic and pancreatic functions (Obici et al, 2001; Pocai et al, 2005; Razavi et al, 2006; Uno et al, 2006; Gram et al, 2007) and the anti-diabetic effects of gastric bypass (Troy et al, 2008).…”
Section: Perspectives In Metabolic Researchmentioning
confidence: 99%